Conflicts Faced By The Losers Club In "It" And "It: Chapter Two" Movies - I Gede Arya Natha Reswara; I Gusti Ayu Gde Sosiowati; Gek Wulan Novi Utami (Jurnal Ilmiah Wahana Pendidikan, 2026)
This research examined conflict as the main force driving character and narrative development in 2017s and 2019s two-part horror films “IT”. This research focused on The Losers Club as they faced various conflicts, with the objectives to find out what types of conflicts The Losers Club characters face in the horror movies “IT” and how they resolve them. Using descriptive qualitative methods, data was collected through documentation and note-taking techniques. Kenney's theory was applied to classify the types of conflict, while Thomas and Kilmann's analyzed conflict management modes. Textual explanations will also be used in presenting the data. The findings showed that all types of conflict, including internal and external (man vs. man, man vs. society, man vs. nature) were found. Meanwhile, almost all modes of conflict management, including competing, compromising, accommodating, and avoiding were found, except collaborating. The results also described how The Losers Club adjusted their strategies to survive each challenge, while also showing the development of their conflict characters as the story reached its climax.